If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3z-2=z-6
We move all terms to the left:
3z-2-(z-6)=0
We get rid of parentheses
3z-z+6-2=0
We add all the numbers together, and all the variables
2z+4=0
We move all terms containing z to the left, all other terms to the right
2z=-4
z=-4/2
z=-2
| 2x-8x+5=2(-3x+6) | | 0=–x^2+2x+4 | | 0=-3x^2+6x+30 | | 64=n+30 | | −c+1.52=8.25 | | 22x^2-50x-48=0 | | n+2/3=9/10 | | 0.81=0.9a | | r/17=-63 | | Y=5x-6/7 | | -3(3x-5)=-3 | | 25x^+30x+9=0 | | 7x-9+2x=2x-23 | | 3(180-x)=8(x-1) | | 0=1/2x+1/5 | | 6(2s-5)=3(s+4) | | 32=17-y | | 4x+180=1080 | | 47.75=5(x-2.95) | | b/5=35 | | x=1.6+0.8 | | n+5.5=17.3 | | 16=-9-1/3x | | m/4+m/8=1 | | 3/4x-5=28 | | -2/11x=-14.5 | | 19.3s=38.6 | | x=2*180 | | -4=y+15 | | (x/2-15)+x=90 | | 4/7=-4/3u | | 1/3^x+-1/4^x+1/12^x=3 |